2017
DOI: 10.2224/sbp.6267
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the predictive factors of cyberbullying in adolescents

Abstract: We examined the factors related to predicting cyberbullying behavior in adolescents, specifically demographics and the use of information and communication technologies. The study participants were 417 adolescents attending high school in Kırşehir, Turkey. We used an individual information form and a cyberbullying scale to collect information and found that 149 (35.7%) of the adolescents had cyberbullied others at least once. Hierarchical regression analysis showed in Step 1 that age, gender, grade, father's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 0 publications
3
28
0
Order By: Relevance
“…Finally, Le et al (2017) identified the composition of the household as a predictor of perpetration behavior (cyber and traditional perpetration was included). However, the other research studies that took this variable into account did not find any relationship between the composition of the household and the probability of being a cybervictim or a cyberbullying perpetrator (Beyazit et al 2017;Doty et al 2017;Uludasdemir and Kucuk 2018).…”
Section: Contextual Family Variablesmentioning
confidence: 88%
See 4 more Smart Citations
“…Finally, Le et al (2017) identified the composition of the household as a predictor of perpetration behavior (cyber and traditional perpetration was included). However, the other research studies that took this variable into account did not find any relationship between the composition of the household and the probability of being a cybervictim or a cyberbullying perpetrator (Beyazit et al 2017;Doty et al 2017;Uludasdemir and Kucuk 2018).…”
Section: Contextual Family Variablesmentioning
confidence: 88%
“…Chen et al (2018) were able to associate the low family income with cybervictimization. On the other hand, Beyazit et al (2017) found that a high family income was a significant factor, predictive of cyberbullying perpetration. On the contrary, Garmy et al (2018) studied the socioeconomic status, identifying three groups according to the degree of affluence (low, medium, and high), and the results were not significant.…”
Section: Contextual Family Variablesmentioning
confidence: 90%
See 3 more Smart Citations